CircKIF5B Promotes Hepatocellular Carcinoma Progression by Regulating the miR-192 Family/XIAP Axis - Fei, Zhenghua; Wang, Yanfen; Gu, Yuyang; Xie, Rongrong; Hao, Qiongyu; Jiang, Yiyan (Frontiers in Oncology, 2022)
Background The long-term prognosis of HCC (hepatocellular carcinoma) with metastasis remains extremely poor. CircRNAs are promising as critical biological markers in identifying disease mechanisms and developing new effective treatments. However, the role of the aberrant expression of circRNAs in HCC progression remains largely unknown. Methods CircKIF5B location was investigated by RNA fluorescence in situ hybridization (RNA-FISH). For circRNA determination, RNase R treatment and Real-Time Quantitative RT-PCR (qRT-PCR) were performed. Transwell chamber assays examined the chemotactic migration and invasion of liver cancer cells. Results This study identified the circRNA circKIF5B originating from exons 1, 2, and 3 of the KIF5B gene. Importantly, we found that circKIF5B circRNA, rather than KIF5B linear mRNA, was notably upregulated in liver cancer cell lines and tissues. Moreover, we found that silencing circKIF5B markedly reduced the proliferation, invasion, and metastasis of liver cancer cells by sponging the miR-192 family, thus decreasing the expression of X-linked inhibitor of apoptosis (XIAP). Conclusion Our data demonstrate that circKIF5B can regulate XIAP expression by sponging miR-192 and miR-215 competing for the ceRNA mechanism, indicating that circKIF5B may act as an essential upstream regulator and providing mechanistic evidence to support the view that circKIF5B/miR-192s/XIAP is a promising therapeutic target for treating liver cancer.